An Investigation of Tooth/Implant-Supported Fixed Prosthesis Designs with Two Different Stress Analysis Methods: An in vitro Study - TuncerBurak ¨Oz¸celik, DDS, PhD;1 and Ahmet Ersan Ersoy, DDS, PhD2 (Journal of Prosthodontics, 2007)
Tooth/implant-supported fixed prostheses (TIFPs) present biomechanical design problems, because the implant is rigidly anchored within the alveolus, and the tooth is attached by the periodontal ligament that allows movement.